From Blueprint to Reality: The Role of AI in Optimizing Sustainable Construction Processes in the Indian Context - Mattoo, Winner (Digital Repository of Theses, 2026)
The construction industry is undergoing a profound transformation driven by the integration of Artificial Intelligence (AI) technologies. However, despite growing global discourse on Construction 4.0, the adoption of AI for sustainable infrastructure development in emerging economies remains limited and uneven. This study investigates how professionals in India’s construction sector perceive, adopt, and experience AI applications in pursuit of sustainability outcomes. A mixed-method research design was employed, combining a nationwide online survey of 106 professionals across 14 states with 12 semi-structured interviews involving project managers, engineers, architects, and sustainability consultants. Data were collected using snowball sampling from professional networks such as the Indian Green Building Council (IGBC), Construction Industry Development Council (CIDC), and LinkedIn communities. Quantitative data were analysed using descriptive and inferential statistics in MS Excel, while qualitative insights were examined through Thematic Analysis following Braun and Clarke’s (2006, 2019) six-phase framework. Findings reveal that AI adoption in construction is primarily driven by perceptions of usefulness, organisational readiness, and sustainability orientation, while barriers include limited digital infrastructure, skill gaps, cost concerns, and regulatory ambiguity. Interview narratives highlight that AI applications such as predictive analytics, energy modelling, and automated design tools enhance project efficiency, waste reduction, and decision-making accuracy. However, adoption remains fragmented, with small and medium enterprises lagging due to technological and cultural inertia. The study contributes to the growing discourse on sustainable digital transformation by offering a contextual understanding of AI-enabled sustainability in the Indian construction ecosystem. It advances both academic and practical knowledge by identifying critical enablers, barriers, and readiness factors, while also informing policymakers and industry leaders seeking to accelerate responsible AI integration in construction practices. Keywords: Artificial Intelligence, Sustainable Construction, Construction 4.0, Thematic Analysis, Digital Transformation, India